THE SUBSTITUTION OF JEWAWUT FLOUR (FOXTAIL MILLET) IN MAKING SEIBI PASTA ROLLS - Titin Hera Widi Handayani, Qirul Qabibah (Prosiding Pendidikan Teknik Boga Busana, 2020)
This objective of was to find out: (1) The best recipe of Seibi Pasta Rolls, (2) the acceptance degree of Seibi Pasta Rolls product and (3) nutritional content of Seibi Pasta Rolls Product. This research was done using R & D (Research and Development) according to 4D method, including: (1) Define is the step to find the best recipe reference each product (2) Design is the step to find the best at substitution level of jewawut flour for each recipe selected reference, (3) Develop is the step to validate the selected recipes for each product (4) Dissemination is step to asses the public acceptance of each product. This research was conducted in culinary Engineering laboratory of Yogyakarta State University on January until April 2019. Analysis data was done using descriptive. The results of this study were: (1) the best recipe of Seibi Pasta Rolls product was jewawut flour : wheat flour (50 : 50), using a mixing, rolling and boiling for making the pasta cover, and sauteing for making the content of pasta and gravy, and the platting using a dinner plate with cheese sauce. (2) test result of sensory panelist for Seibi Pasta Rolls in terms the colour, aroma, texture and flavor was categorized in the preferred and very-preferred and (3) nutritional content of Seibi Pasta Rolls product based on the proximate test. Keywords: Jewawut Flour, Foxtail Millet, Pasta, Seibi Pasta Rol